Analisis Jalālah Dalam Sunnah: Studi Hermeneutika Perspektif Zaghloul Al-Najjar - Chaerul Umam Shabran; Achmad Abubakar; Muhsin Mahfudz (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
Prophetic traditions related to dietary practices do not merely convey legal rulings but also reflect concern for human health and well-being. One such tradition is the prohibition of consuming jalālah, animals that habitually feed on impurities. In the context of modern scientific developments, phenomena such as Bovine Spongiform Encephalopathy (BSE), commonly known as mad cow disease, provide a new perspective for understanding this prohibition, particularly in relation to food safety and environmental health. This study aims to examine the meaning of the hadith concerning jalālah through the perspective of Zaghloul an-Najjar and to explore its relevance to contemporary scientific findings. The results indicate that the prohibition is not solely normative in nature but also embodies a preventive dimension in safeguarding the quality of consumption. The scientific exegesis approach demonstrates a correspondence between the prophetic message and modern health principles, especially regarding the risks associated with contaminated food chains. Furthermore, the differences of opinion among Islamic jurists concerning the legal status of jalālah reflect the dynamic and contextual nature of hadith interpretation. Therefore, this study affirms that prophetic traditions possess a universal dimension that remains relevant in addressing contemporary issues related to health and human life.